Nuclear expression of the 50- and 65-kD Rel-related subunits of nuclear factor-kappa B is differentially regulated in human monocytic cells. - Kaufman, P A; Weinberg, J B; Greene, W C (The Journal of Clinical Investigation, 1992)
The nuclear factor (NF)-kappa B transcription factor system is composed of at least four inducible nucleoprotein adducts termed p50, p55 (NF-kappa B p50), p75 (NF-kappa B p65), and p85 (c-Rel). These proteins are expressed in the nuclei of activated T cells in a distinctly biphasic fashion, with p55 and p75 induction occurring within minutes whereas the induction of p50 and p85 occurs after several hours. In contrast, p50 and p55 are constitutively expressed in the nuclei of U937 and THP-1 monocytic cells. However, cellular activation is required for the nuclear expression of p75 in these cells. Additionally, activation of monocytic cells does not result in a significant induction of p85. Tumor necrosis factor alpha induces the nuclear expression of p55 and p75 in these monocytic cells within 20 min, presumably reflecting the liberation of these proteins from I kappa B. In contrast, phorbol myristate acetate (PMA) induces the expression of these proteins with delayed kinetics, raising the possibility that PMA is incapable of mediating the efficient release of p55 and p75 from I kappa B in these cells. These findings highlight important differences in the regulation of these proteins in monocytic cells versus T cells and suggest that the induced expression of NF-kappa B p65 in monocytes may play a central role in the activation of HIV-1 gene expression. Images